2018
DOI: 10.1021/acs.est.7b06551
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sulfur Reduction To Generate H2S As a Reducing Agent To Achieve Simultaneous Catalytic Removal of SO2 and NO and Sulfur Recovery from Flue Gas

Abstract: The conventional flue gas treatment technologies require high capital investments and chemical costs, which limit their application in industrial sectors. This study developed a sulfur-cycling technology to integrate sulfide production by biological sulfur reduction and simultaneous catalytic desulfurization and denitrification with HS (HS-SCDD) for flue gas treatment and sulfur recovery. In a packed bed reactor, high-rate sulfide production (1.63 ± 0.16 kg S/m-d) from biological sulfur reduction was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…This process causes the enhancement of the aeration equipment and energy consumption. Another method of desulfurization is to reduce SO 2 to elemental sulfur for recovery. The inherent deficiency of this method is the requirement of gaseous reducing agents and a high reaction temperature, inhibiting the further commercialization in the removal of SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This process causes the enhancement of the aeration equipment and energy consumption. Another method of desulfurization is to reduce SO 2 to elemental sulfur for recovery. The inherent deficiency of this method is the requirement of gaseous reducing agents and a high reaction temperature, inhibiting the further commercialization in the removal of SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, a promising bioscrubbing process is presented herein to valorise pollutants such as SO2 contained in flue gases as elemental sulfur. This novel bio-FGD alternative is based on the sequential absorption of SO2 and NOx from flue gas in two consecutive scrubbers, coupled to the biological treatment of sulphate/sulphite and nitrate/nitrite contained in scrubbing liquors (Philip and Deshusses 2003;Wang et al 2013;Sun et al 2018). Biological treatment of the resulting sulphate/sulphite rich-streams is performed through a two-steps bioprocess consisting of sulphate/sulphite biological reduction to H2S followed by its partial oxidation to elemental sulphur under anoxic conditions using nitrate/nitrite rich-stream as electron acceptor.…”
mentioning
confidence: 99%
“…The biological reduction of sulfate contained in AMD allows precipitating metals with sulfide to afterwards be valorized or not depending on the added value of the recovered metals (Christensen et al, 1996;Jong and Parry, 2003;Neculita et al, 2007). Apart from this last application, only few studies can be found in the literature focused on sulfur recovery from SOx emissions or S-rich effluents (Chuang et al, 2005;Jiang et al, 2013;Sun et al, 2018;Zhang et al, 2018), and most of them require either using easily biodegradable and/or expensive carbon resources or treating low S loads (< 2 kg m -3 d -1 ). Jiang et al (2013) reported excellent results applying the SANI process although required sewage and nitrogen sources to valorize S-containing effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al (2013) reported excellent results applying the SANI process although required sewage and nitrogen sources to valorize S-containing effluents. Zhang et al (2018) reported a smart alternative to the SANI process, targeting biosulfur production, to treat specifically sulfate-deficit wastewater and also required the use of domestic wastewater for sulfate reduction; and Sun et al (2018) developed a novel bio-FGD system configuration to eliminate SO2 and NO from flue gases although requiring the application of a quartz sulfur condenser to separate the final product and concluding that, the process could be profitable if the operational parameters could be further optimized and if wastewater was available. Other studies propose both biological steps (sulfate reduction and sulfide oxidation) in a single reactor with successful results and less investment costs but probably with complex downstream procedures for sulfur recovery or low sulfur purities (Philip and Deshusses, 2003;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%